Avaliação da qualidade físico-hídrico-mecânica de um latossolo vermelho sob diferentes manejos - Koppe, Ezequiel (2014)
Different systems use and management tend to degrade the soil structure. The reduction of soil physical quality has direct consequences for the growth and development of plants, as well as the dynamic flow of water and nutrients. The objective of this study was evaluate the effects of different systems of use and management in the flow and availability of soil water, to quantify the effects of management practices on the physical-mechanical properties of the soil and what is the response of plants due to handling. The systems that were analyzed are: i) integrated crop livestock (ICL), ii) continuous no-tillage (NT), for a period exceeding 15 years, iii) chisel plow tillage (T+CP ) iv) tillage scarified with a harrowing (T+S+H). v) native Forest (FOREST) six layers of soil (0,00-0,05, 0,05-0,10, 0,10-0,15 were evaluated, 0,15-0,20, 0,20-0,30 and 0,30-0,40 m). The FOREST showed the highest infiltration rates (5200 mm h-1), and the greater amount of water available (0,31 m³ m-3) and was the FOREST that had the highest value of the index S. The ICL system was the system that had the lowest infiltration rates (140 mm h-1), the lowest values of available water (0,09 m3 m-3) and the system T+CP showed lower index S. The physical-mechanicalattributes of FOREST soil, presents the largest pore volume, the higher pressure pre-consolidation, the lowest density, the lowest maximum density, the relative density and a the lower rate of compression. The mechanical intervention promotes the reducing of compression state, and these effects are longer than 320 days. The agricultural systems where no tillage demonstrate the formation of a compacted subsurface layer (0,05-0,20 m). The growth and development of plants was higher in T+CP and T+S+H, with the largest number of nodes per stem and greater in number of productive nodes was found in these systems. The highest yield was found in the NT system (3.548 kg) and the lowest yield was found in the ICL system (2.821 kg). The FOREST presents the best water conditions, especially because there are no human actions and presents a low compression state. The mechanical intervention favors the water infiltration and low S index, also promoting increased values of porosity and compression index. The NT and ICL systems, due to the period of 15 years without tillage, combined with high traffic of machinery and animal trampling exhibit more compacted, consequently lower rate of infiltration and water availability and reduced values of S index, also have high values of pre-consolidationpressure, of soil density, of relative density and compression rate. The tillage system with straw in high quantity is effective in maintaining higher yield of soybean. The mechanical intervention provides a favorable environment for the growth and development of plants.